2001
DOI: 10.1093/ajcn/73.3.613
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of plasma total homocysteine concentration in the Framingham Offspring cohort

Abstract: Our study confirmed, in a population-based setting, the importance of the known determinants of fasting tHcy and suggested that other dietary and lifestyle factors, including vitamin B-6, riboflavin, alcohol, and caffeine intakes as well as smoking and hypertension, influence circulating tHcy concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

50
366
13
34

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 574 publications
(463 citation statements)
references
References 42 publications
50
366
13
34
Order By: Relevance
“…Our results do not support an effect of increased adipose mass on plasma homocysteine concentrations. These results are in agreement with other published work [45,46], although some authors have found a weak correlation between plasma homocysteine and BMI [47]. Fibrinogen, CRP and vWF were negatively correlated with the QUICKI index.…”
Section: Discussionsupporting
confidence: 93%
“…Our results do not support an effect of increased adipose mass on plasma homocysteine concentrations. These results are in agreement with other published work [45,46], although some authors have found a weak correlation between plasma homocysteine and BMI [47]. Fibrinogen, CRP and vWF were negatively correlated with the QUICKI index.…”
Section: Discussionsupporting
confidence: 93%
“…Vitamin deficiency is among the principal causes of elevated tHcy in the general population (Selhub et al, 1993;Clarke & Armitage, 2000). In addition to diet, other lifestyle factors such as smoking, physical activity, and consumption of alcohol, coffee and tea may have an effect on tHcy concentrations in the general population (Nygard et al, 1995(Nygard et al, , 1997(Nygard et al, , 1998Ubbink et al, 1998;Rasmussen et al, 2000;De Bree et al, 2001a;Jacques et al, 2001;Koehler et al, 2001;Mayer et al, 2001;Saw et al, 2001). The thermolabile variant of the methylenetetrahydrofolate reductase (MTHFR(C677T)), a regulating enzyme in tHcy metabolism, is an important genetic determinant of tHcy (Frosst et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have explored the associations between tHcy and multiple lifestyle factors in large representative samples of the general population (Nygard et al, 1995(Nygard et al, , 1998De Bree et al, 2001a;Jacques et al, 2001). However, these studies have not adjusted for the confounding effects of the MTHFR(C677T) polymorphism nor considered the potential gene-lifestyle interactions.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that unfiltered coffee increases plasma homocysteine concentrations in people with normal baseline concentrations. 2,4,5,11,12 Randomized clinical trials suggest that there is a homocysteine-raising effect of both filtered 13 and unfiltered coffee. 2 However, coffee intake in these studies was high (1 l per day) and at these levels of consumption, our results agree with the results of the above studies.…”
Section: Discussionmentioning
confidence: 99%
“…1 A randomized clinical trial 3 and some population studies have suggested that a high intake of coffee is associated with raised concentrations of plasma homocysteine. 4,5 On the other hand, no association between coffee consumption and plasma homocysteine levels was observed in participants of the Atherosclerosis Risk in Communities (ARIC) study. 6 These discrepant findings may be attributed to the quantity and type of coffee consumed.…”
Section: Introductionmentioning
confidence: 99%